Indications and associated outcomes for platelet-rich plasma injections performed in an academic orthopaedic-specific hospital: A patient satisfaction survey. Issue 3 (27th May 2020) - Melbourne, Craig S.; Smith, Conor A.; Patel, Jaykumar; Platt, Brooks; Cook, James L.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Platelet-rich plasma (PRP) is an autologous biologic product that has become widely used in orthopaedic centers and at so-called "regenerative medicine" or "pain" clinics. Although food Drug Administration (FDA)-approved indications for use of PRP in orthopaedics are for applications in which it is mixed with autograft or allograft bone, attention and clinical research have focused on its off-label uses for treatment of osteoarthritis, musculotendinous disorders, or joint pain. The present study aimed to document indications for PRP used by orthopaedic surgery faculty in an academic orthopaedic-specific hospital between 2011 and 2016, characterize demographics of patients receiving these injections, and assess associated 1-year or greater outcomes for these patients. Methods: With institutional review board approval, this study retrospectively identified 148 patients with osteoarthritis, augmentation surgical treatments, tendon or ligament pathology, and sacroiliac joint pain as indications for PRP treatment. Results: For respondents (n=60), 78.3% (47 of 60) reported PRP-related improvement in symptoms, with mean duration of effect of 800 days and an overall level of satisfaction with their PRP treatment of 67.9% (range, 1-100%). Factors that negatively influenced successful outcomes in the present study included patient age older than 45 yr and use of leukocyte-rich PRP, while degree of improvement and return to full activity positively influenced patient satisfaction with PRP treatment. Conclusions: The results of the present study suggest that PRP can be used to treat a variety of musculoskeletal conditions commonly diagnosed at an academic orthopaedic-specific hospital, with expectations for 78% of patients reporting improvement and an overall patient satisfaction level of 68%. Level of Evidence: Level IV.